“A todo evento”: argumentación jurídica e (in)comunicación profesional (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
“A todo evento” [“In any event”] is an archaic and rare expression, which at present is only used occasionally in general, ordinary or standard Spanish; however, it is usually used as a connective device in legal texts. This expression is employed to introduce an argument carrying the same argumentative orientation as those developed before it, but presented as the most important one in the series, as an “apparently” unquestionable argument. By analyzing a corpus made up of 100 (one hundred) questionnaires answered by prospective candidates to judgeships in the Judiciary of the Province of Buenos Aires (Argentina), this article aims at showing how, despite their education and prior experience, candidates mistake and even appear to be unaware of what “a todo evento” means and how it is used, beyond its most frequent usage. This shows, once again, that the communication problems identified in legal texts not only affect ordinary citizens with no knowledge of the Law, but also legal practitioners themselves.
Keywords: legal language; “a todo evento”; legal argumentation; professional communication